Penegakan dan Kewajiban Penerapan Hukum Asing dalam Peradilan Indonesia: Suatu Tinjauan Yuridis - Megi, Megi Mardian (Palangka Law Review, 2024)
This article discusses the legal use of foreign law by Indonesian courts based on Indonesian International Private Law (HPI). This review is based on various HPI-related laws and regulations, court decisions, and HPI textbooks. The survey results show that there are often judges who do not follow the principle of ius curia novit in using foreign law; considering external factors of Indonesian law and cases, even though the HPI provisions refer to foreign law. Therefore, the Indonesian HPI Law must be promulgated immediately so that Indonesian courts have no reason to ignore the use of foreign law. In addition, it is necessary to build a system that helps judges and courts access foreign country laws and regulations quickly and accurately. International cooperation between the Supreme Court of the Republic of Indonesia (MARI) and the Supreme Court or courts of other countries must also be considered in the exchange of foreign legal information.